Neue Cassidinen aus China (Coleoptera: Chrysomelidae). - Medvedev, Lev N. (Contributions to Entomology = Beiträge zur Entomologie, 1957)
The results of the treatment of Chinese Cassidinae from the author’s collection are discussed. There are described 3 new species, 2 new subspecies, and mentioned species new to China. Types and Paratypes in the collection of the Zool. Inst. Acad. Sei. USSR and in the author’s collection. Nomenclatural Acts gresitti [sic!] Medvedev, 1957 (Basiprionota), spec. n. mongolensis Medvedev, 1957 (Cassida prasina), sspec. n. hincksi Medvedev, 1957 (Cassioa Mionycha), spec. n. gansuica Medvedev, 1957 (Glyphocassis spilota), sspec. n. pygmaea Medvedev, 1957 (Thlaspida), spec. n.